2017
DOI: 10.1016/j.celrep.2017.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Plexin B2 and Semaphorin 4C Guide T Cell Recruitment and Function in the Germinal Center

Abstract: Follicular T helper (T) cells orchestrate the germinal center (GC) response locally. T localization in GCs is controlled by chemo-guidance cues and antigen-specific adhesion. Here. we define an antigen-independent, contact-dependent, adhesive guidance system for T cells. Unusual for amoeboid cell migration, the system is composed of transmembrane plexin B2 (PlxnB2) molecule, which is highly expressed by GC B cells, and its transmembrane binding partner semaphorin 4C (Sema4C), which is upregulated on T cells. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 60 publications
1
31
1
Order By: Relevance
“…GC B cells robustly express plexin B (PlxnB), which interacts with its binding partner semaphorin 4C (Sema4C) that is upregulated by GC Tfh cells. 68 This interaction promotes adhesion and entanglement between GC Tfh and B cells and is thought to guide Sema4C-expressing Tfh cells for retention in the PlxnB-rich GC. 68 In contrast, ephrin B1 (EFNB1) on GC B cells, signaling through Ephrin type-B receptor 6 (EPHB6) on the T cells, inhibits adhesion with GC Tfh cells, which in turn limit GC retention of Tfh cells.…”
Section: Germinal Center Tfh Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…GC B cells robustly express plexin B (PlxnB), which interacts with its binding partner semaphorin 4C (Sema4C) that is upregulated by GC Tfh cells. 68 This interaction promotes adhesion and entanglement between GC Tfh and B cells and is thought to guide Sema4C-expressing Tfh cells for retention in the PlxnB-rich GC. 68 In contrast, ephrin B1 (EFNB1) on GC B cells, signaling through Ephrin type-B receptor 6 (EPHB6) on the T cells, inhibits adhesion with GC Tfh cells, which in turn limit GC retention of Tfh cells.…”
Section: Germinal Center Tfh Cellsmentioning
confidence: 99%
“…GC B cells ro-bustly express plexin B (PlxnB), which interacts with its binding partner semaphorin 4C (Sema4C) that is upregulated by GC Tfh cells 68. GC B cells ro-bustly express plexin B (PlxnB), which interacts with its binding partner semaphorin 4C (Sema4C) that is upregulated by GC Tfh cells 68.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…138 In addition, Plexin B2 (PlxnB2) was found to be highly expressed in GC B cells in a T-cell-dependent manner together with other axon guidance genes, such as BASP1. 139,140 The PlxnB2 ligand, Sema4C is specifically expressed in Tfh cells and increased surface expression resulted in effective positioning of Tfh cells in the GC.…”
Section: Additional Molecul Ar Mechanis Ms That Reg Ul Ate T and B mentioning
confidence: 99%
“…These findings suggest that the Sema4C:PlxnB2 interactions might potentiate TCR signaling and integrin-mediated adhesion at the T-B synapse. 140 In addition to positive mechanisms evolved to prolong T-cell in- Ephrin-B1. 141,142 In a cytometry based cell-cell conjugate assay, it was demonstrated that T-cell interactions with highly Ephrin-B1expressing B cells was reduced compared to non-transduced control cells, in an antigen-specific manner.…”
Section: Additional Molecul Ar Mechanis Ms That Reg Ul Ate T and B mentioning
confidence: 99%